Evaluation of QoS in RF/Li-Fi hybrid networks on 5th generation environments - Rodríguez-Fonseca, Andrés Alexander; Paternina-Durán, Jesús Manuel; Salcedo-Parra, Octavio José (Universidad Pedagógica y Tecnológica de Colombia, 2017)
This paper evaluates the most relevant scenarios in which establishing QoS parameters on RF/Li-Fi hybrid networks is necessary. The objective is to determine the improvement possibilities provided by this technology and realistically value its development potential, specifically for services in real time. We reviewed the alternatives in Internet of Things (IoT), applications, load balancing, scenarios of 5th generation, wireless sensors, and security, in addition to simulations and architectures of technology interoperability.